PELATIHAN PENGGUNAAN FLASHCARDS BERBASIS DEEP LEARNING BAGI GURU BAHASA INGGRIS UNTUK PENGUATAN SPEAKING DAN PENGUASAAN KOSAKATA SISWA SMP/SMA LOMBOK UTARA - Fitri, Surni Ahyatul; Junaidi, Ahmad; Maulidi, Harish (Unpad Press, 2026)
Limited vocabulary mastery and speaking proficiency among junior and senior high school students in North Lombok Regency are closely linked to English teachers' constrained pedagogical competence in designing meaningful and communicative instruction, particularly in a tourism-oriented region that demands strong English skills among the younger generation. This community service program aimed to strengthen teachers' competence in implementing Deep Learning-based instruction through the use of flashcards to reinforce students' vocabulary and speaking skills. The program employed training, workshops, teaching simulations (microteaching), and mentoring, conducted in three stages—needs orientation and analysis, pedagogical competence reinforcement, and flashcards implementation—involving 20 teachers at the socialization stage and an average of 15 active participants across eight sessions from April to June 2026. Diagnostic test results revealed that 85% of participants scored below 70 in grammar, indicating an urgent need for linguistic and pedagogical strengthening. Through the training, teachers successfully designed diverse flashcard-based learning activities, including Board Race Vocabulary, Word Categorization, and dialogue construction, reflecting increased creativity and confidence in creating interactive, student-centered instruction. The program concludes that integrating flashcards with a Deep Learning approach effectively fosters more contextual and communicative teaching practices, contributing to the sustainable improvement of English language instruction quality in North Lombok Regency.